BENEFITS OF EARLY CHILDHOOD EDUCATION FOR PERSONAL DEVELOPMENT AND CHILDREN SOCIAL (Universitas Negeri Semarang, 2012)
Early childhood is a new child is born until the age of 6 years. Determine the age of the formation of character and personality of children. Early Childhood Education, there are three forms of the lines: (1) formal education, (2) non-formal education, (3) informal education. Constraints early childhood are the knowledge and the readiness of parents toeducate children is not well grounded in developmental psychology, which in the preferred activity of children, to educate the maximum. This problem is: how do the benefits of early childhood education for personal and social development of children? Erikson, explained the concept of personal and social development theory, developed a multilevel polarity. There are 8 (eight) stage of development. Every level, every personwill experience a conflict / crisis as a turning point in development. The conflict centers on the development of psychological quality or failing to develop the quality. Theory of personal and social development in early childhood Erikson only up to 4 stages, namely: (1) Trust vs. Mistrust, (2) Autonomy vs. shame and doubt, (3) Initiative vs. Guilt (4) Industry vs. inferiority. Supported early childhood development benefits, it will bedirected to build a feeling competent and confident in their skills. When switching to the middle and late childhood, then it will direct its energy towards the acquisition of knowledge, intellectual skills.